The Role of Inflammatory Markers for Risk Stratification and Prognosis in Dialysis Patients: A Narrative Review - Siti Liyana Mohd Nor; Mohd Radzniwan A Rashid; Faizul Helmi Addnan; Siva Gowri Patmanathan; Nizam Baharom; Sharifah Najwa Syed Mohamad; Ruslinda Mustafar; Saharudin Ahmad; Arifa Mustika; Minidian Fasitasari; Lusito Lusito (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Science Health & Technology, Volume 11 Issue 2 Page (236-248)